How to prove that: `sin^2xcos^3x=(sin^2x-sin^4x)cosx`

Asked on by farajallah

2 Answers | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

The identity `sin^2xcos^3x=(sin^2x-sin^4x)cosx` has to be proved.

Start with the left hand side


= `sin^2x*cos^2x*cos x`

= `sin^2x*(1 - sin^2x)*cosx`

= `(sin^2x - sin^4x)*cos x`

This proves that `sin^2xcos^3x=(sin^2x-sin^4x)cosx`

We’ve answered 319,865 questions. We can answer yours, too.

Ask a question